Race, Ethnicity, and Clinical Outcomes in Hormone Receptor-Positive, HER2-Negative, Node-Negative Breast Cancer in the Randomized TAILORx Trial. (28th September 2020) - Albain, Kathy S; Gray, Robert J; Makower, Della F; Faghih, Amir; Hayes, Daniel F; Geyer, Charles E; Dees, Elizabeth C; Goetz, Matthew P; Olson, John A; Lively, Tracy; Badve, Sunil S; Saphner, Thomas J; et al.
Abstract: Background: Black race is associated with worse outcomes in early breast cancer. We evaluated clinicopathologic characteristics, the 21-gene recurrence score (RS), treatment delivered, and clinical outcomes by race and ethnicity among women who participated in the Trial Assigning Individualized Options for Treatment. Methods: The association between clinical outcomes and race (White, Black, Asian, other or unknown) and ethnicity (Hispanic vs non-Hispanic) was examined using proportional hazards models. All P values are 2-sided. Results: Of 9719 eligible women with hormone receptor–positive, HER2-negative, node-negative breast cancer, there were 8189 (84.3%) Whites, 693 (7.1%) Blacks, 405 (4.2%) Asians, and 432 (4.4%) with other or unknown race. Regarding ethnicity, 889 (9.1%) were Hispanic. There were no substantial differences in RS or ESR1, PGR, or HER2 RNA expression by race or ethnicity. After adjustment for other covariates, compared with White race, Black race was associated with higher distant recurrence rates (hazard ratio [HR] = 1.60, 95% confidence intervals [CI] = 1.07 to 2.41) and worse overall survival in the RS 11-25 cohort (HR = 1.51, 95% CI = 1.06 to 2.15) and entire population (HR = 1.41, 95% CI = 1.05 to 1.90). Hispanic ethnicity and Asian race were associated with better outcomes. There was no evidence of chemotherapy benefit for any racial or ethnic group in those with a RS of 11-25. Conclusions: Black women had worse clinical outcomes despite similar 21-gene assay RS results and comparable systemic therapy in the Trial Assigning Individualized Options for Treatment. Similar to Whites, Black women did not benefit from adjuvant chemotherapy if the 21-gene RS was 11-25. Further research is required to elucidate the basis for this racial disparity in prognosis.